Sistema computacional para índices de cárie dentária: banco de dados e análise estatística A computer software system for dental caries rates: data bases and statistical analysis - Maria Lucia M.M. Sundefeld; Sabina Léa Davidson Gotlieb (Universidade de São Paulo, 1996)
Apresenta-se um sistema computacional, denominado ICADPLUS, desenvolvido para elaboração de banco de dados, tabulação de dados, cálculo do índice CPO e análise estatística para estimação de intervalos de confiança e comparação de resultados de duas populações.Tem como objetivo apresentar método simplificado para atender necessidades de serviços de saúde na área de odontologia processando fichas utilizadas por cirurgiões dentistas em levantamentos epidemiológicos de cárie dentária. A característica principal do sistema é a dispensa de profissional especializado na área de odontologia e computação, exigindo o conhecimento mínimo de digitação por parte do usuário, pois apresenta "menus" simples e claros como também relatórios padronizados, sem possibilidade de erro. Possui opções para fichas de CPO segundo Klein e Palmer, CPO proposto pela OMS, CPOS segundo Klein, Palmer e Knutson, e ceo. A validação do sistema foi feita por comparação com outros métodos, permitindo recomendar sua adoção. A computer software system developed ICADAPLUS, is presented in order to create and tabulate data bases, calculate the DMF rate, perform statistical comparison of two populations, and calculate confidence intervals. The system offers a simplified method for health services in the area of dentistry, using dental records to carry out epidemiological surveys of tooth decay. The system's main feature is that it does not require specialists either in the area of dentistry or computing, demanding of the user only basic data-entry typing skills, since it presents simple menus, and standardized reports, with no possibility of error.The system comprises four steps: Data-entry, Processing, Reports and Utilities. In Data-entry the regions, towns and institutions supplying the data are initially registered, once only. Each record receives a code number, and it is this code which is available to the user through a Function Key, by means of which the code is transferred to the desired data field. Furthermore, there is a choice of type of dental chart: Klein and Palmer's DMF; the DMF proposed by the WHO; Klein, Palmer and Knutson's DMF surfaces; or Gruebbel's def.It is possible to include, alter and exclude records in each option. In Processing, it is necessary, first of all, to organise the indexes, totalize the data, and remit them to the data base, where no further alteration or exclusion occurs. From this stage on, reports can be prepared from the proposed indexes, grouped according to age, or age and gender. The system was validated by comparison with other methods. This comparison justifies the recomendation of its implementation.